PROCESS ANALYTICAL TECHNOLOGY IMPLEMENTATIONPROGRESSION FOR A PHARMACEUTICAL INDUSTRY - SARAVANA KUMAR .V,; P.SHANMUGASUNDARAM, (International Journal of Pharma and Bio Sciences, 2014)
Process Analytical Technology (PAT) has been introduced as an advent of new tool which has given an opportunity for all the pharmaceutical manufacturers to improve upon their quality and compliance. The application of this technology in pharmaceutical manufacturing ensures the quality of raw material attributes that too at-line, in-line or online, which was difficult earlier, thereby decreasing the chances of error and significant savings in time required for testing. In Total, Process Analytical Technology lays a way for producing a standard product which is in line with Quality and thus creating a satisfaction with customer needs and making a good brand image for the organization. In this article, Process Analytical Technology has been introduced briefly and explained its different tool in order to illustrate how application of this technology ensures quality of pharmaceutical products and implementation will enhance the organization image.